PENGARUH PELAKSANAAN KEBIJAKAN DANA DESA TERHADAP MANAJEMEN KEUANGAN DESA DALAM MENINGKATKAN EFEKTIVITAS PROGRAM PEMBANGUNAN DESA - Kumpas, Nur Fadhilah I.; Liastri, Riska Adriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The purpose of writing this research is to discuss the effect of implementing Village Fund policies on Village financial management in increasing the effectiveness of Village development programs. The analytical method used in discussing the main topics uses a causal effectual analysis model by reviewing rational relationships that analyze the causal relationship between the implementation of Village Fund policies, Village financial management and the effectiveness of Village development programs. The research location was in villages throughout the Garut Regency which were sampled based on the sub-district typology where the village was located, with a total of 80 respondents. The results of the discussion show that the implementation of the Village Fund policy has a real and positive effect on village financial management and the effectiveness of village development programs. This study concludes that for the proper implementation of Village Fund policies, this can be done by realizing Village financial management so as to increase the effectiveness of Village development programs.